Full-color micro-LED display with photo-patternable and highly ambient-stable perovskite quantum dot/siloxane composite as color conversion layers - Hyung Cheoul Shim; Juho Kim; So Yeon Park; Bong Sung Kim; Bongkyun Jang; Hak-Joo Lee; Areum Kim; Seungmin Hyun; Jae-Hyun Kim (Scientific Reports, 2023)
Abstract In this paper, we successfully fabricated color conversion layers (CCLs) for full-color-mico-LED display using a perovskite quantum dot (PQD)/siloxane composite by ligand exchanged PQD with silane composite followed by surface activation by an addition of halide-anion containing salt. Due to this surface activation, it was possible to construct the PQD surface with a silane ligand using a non-polar organic solvent that does not damage the PQD. As a result, the ligand-exchanged PQD with a silane compound exhibited high dispersibility in the siloxane matrix and excellent atmospheric stability due to sol–gel condensation. Based on highly ambient stable PQD/siloxane composite based CCLs, full-color micro-LED display has a 1 mm pixel pitch, about 25.4 pixels per inch (PPI) resolution was achieved. In addition, due to the thin thickness of the black matrix to prevent blue light interference, the possibility of a flexible display that can be operated without damage even with a bending radius of 5 mm was demonstrated.